Assessment of physical preparation in basketball - S. Suárez (Federación Extremeña de Balonmano; University of Extremadura, 2016)
Physical preparation continuous and integrated into a basketball team is essential to achieve the objectives set at the beginning of the season. This study shows the evaluation of physical preparation work on a basketball team in the province of Huelva in the cadet category. Therefore has carried out an analysis of the records of the parties that faced the team of CB Ciudad de Huelva, against Marist A, CB Lepe Alius 2001, CB Lepe Alius 2000 and CB La Palma 95 of the cadet category , league province of Huelva . In addition to conducting some interviews with players C.B City of Huelva and sports coordinator of the club. In light of the results it seems essential to conduct a comprehensive physical preparation and continuing throughout the season . As long as this well-planned , individualized and adapted.